Mn-rich chondrule rims in CO3 chondrites: Implications for the composition of nebular dust - Jillian Kirk; Myriam Telus; Pranvera Hyseni; Fatima Jorge-Chavez; Vanessa Mendoza; Steven J. Desch; Dale Burns; Steven Simon (Icarus, 2026)

Urban climate evaluation in the upcoming generation of CMIP6-Driven EURO-CORDEX regional climate simulations - Javier Diez-Sierra; Natalia Zazulie; Gaby S. Langendijk; Yaiza Quintana; Marianna Adinolfi; May Bohmann; Lars Buntemeyer; Erasmo Buonomo; Steven Caluwaerts; Angelo Campanale; Rita M. Cardoso; David Carvalho; et al. (Urban Climate, 2026)

Pilot-scale production of microbial protein and PHA using purple phototrophic bacteria for single-cell bioplastics - Luis D. Allegue; Sergio J. Gonzalez Camara; Maarten Muys; Shreyash Anil Gujar; Steven De Meester; Leen Bastiaens; Queenie Simons; Heleen De Wever; Joost Brancart; Siegfried E. Vlaeminck (Bioresource Technology Reports, 2026)

Which soil health indicators best track diversification benefits in tropical agroecosystems? - Anna M. Visscher; Simon Fonteyne; Mirjam Pulleman; Anna Alekseeva; Martin Hartmann; Jose M. Rodriguez-Castellanos; Pankaj Trivedi; Rodolfo Vilchis-Ramos; Sergio Zapata-Martínez; Bruce G. Ferguson; Helda Morales; Steven Vanek; et al. (Applied Soil Ecology, 2026)

Evaluating MXene-doped PEDOT coating on carbon fiber microelectrodes for dual-functional neural interfacing - Sorel E. De León; Rana Jaylani; Young Jun Jung; Negin Jalilinejad; Toon Goris; Simon Higham; Kate Fox; Michael Ibbotson; Steven Prawer; Shadi Houshyar; Wei Tong; David J. Garrett (Analytica Chimica Acta, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Greater recalled pain and movement-evoked pain are associated with longer 400-m walk and repeat stair climb timein older adults: the study of muscle, mobility, and aging - Theresa Mau; Corey B. Simon; Haley N. Barnes; Megan Hetherington-Rauth; Scott R. Bauer; Elsa S. Strotmeyer; Nancy E. Lane; Michael C. Rowbotham; Ashley A. Weaver; Terri L. Blackwell; Yurun Cai; Nancy W. Glynn; et al. (GeroScience, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

A Conceptual Framework and Methods for Studying the Connectivity of Fishes - Jordanna N. Bergman; Jessica A. Robichaud; Jasper McCutcheon; Michael T. Booth; Brendan Campbell; Grace A. Casselberry; Cienna R. Cooper; Bronwyn M. Gillanders; Lucas P. Griffin; Edward Hale; Luc LaRochelle; Karen J. Murchie; et al. (Fish and Fisheries, 2026)
Connectivity is a multifaceted concept that has important implications for the management and conservation of marine and freshwater fishes. We developed a conceptual framework that encompasses multiple, interrelated categories of connectedness, including landscape (e.g., structural, functional) connectivity and ecological (e.g., trophic, genetic, demographic) connectivity, that together shape the flow of organisms, energy and information across ecosystems. We also synthesised six key methods that can be used to study connectivity of fishes: (1) telemetry, including satellite, acoustic, radio and passive integrated transponders (PIT), (2) mark‐recapture, (3) environmental tracers, including stable isotopes and otolith‐microchemistry, (4) genetics, (5) community structure analysis and (6) emerging technologies and tools (e.g., remote sensing and artificial intelligence). For each method, we describe the categories of connectivity it can assess and provide real‐world examples where they have been effectively used. We also identify limitations of each method. This article highlights the diverse and evolving toolbox of methods used to assess fish connectivity, underscoring the need for continued collaboration, innovation and integration of new approaches to refine our understanding and address remaining challenges in this critical area of aquatic ecology and fisheries management.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Scaling carbon capture and storage (CCS) to gigaton capacity: A multi-dimensional and critical review - Benjamin Mitterrutzner; Benjamin K. Sovacool; Brage Rugstad Knudsen; Morgan D. Bazilian; Jinsoo Kim; Simon Roussanaly; Asgeir Tomasgard; Steven Griffiths (International Journal of Greenhouse Gas Control, 2026)

The social welfare value of the global food system - Simon Dietz; Benjamin Bodirsky; Michael Crawford; Ravi Kanbur; Debbora Leip; Steven Lord; Hermann Lotze-Campen; Alexander Popp (Ecological Economics, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

A method to identify positive tipping points to accelerate low-carbon transitions and actions to trigger them - Timothy M. Lenton; Thomas W. R. Powell; Steven R. Smith; Frank W. Geels; Floor Alkemade; Martina Ayoub; Pete Barbrook-Johnson; Scarlett Benson; Fenna Blomsma; Chris A. Boulton; Joshua E. Buxton; Sara M. Constantino; et al. (Sustainability Science, 2026)
Meeting the Paris Agreement to limit global warming to “well below 2 °C” requires a radical acceleration of action, as the global economy is decarbonising at least five times too slowly. Tipping points, where low-carbon transitions become self-propelling, could be key to achieving the necessary acceleration. We deem these normatively ‘positive’, because they can limit considerable, inequitable harms from global warming and help achieve sustainability. Some positive tipping points, such as the UK’s elimination of coal power, have already been reached at national and sectoral scales. The challenge now is to credibly identify further potential positive tipping points, and the actions that can bring them forward, whilst avoiding wishful thinking about their existence, or oversimplification of their nature, drivers, and impacts. Hence, we propose a methodology for identifying potential positive tipping points, assessing their proximity, identifying the factors that can influence them, and the actions that can trigger them. Building on relevant research, this ‘identifying positive tipping points’ (IPTiP) methodology aims to establish a common framework that we invite fellow researchers to help refine, and practitioners to apply. To that end, we offer suggestions for further work to improve it and make it more applicable.

Environmental and Geographic Conditions on the Breeding Grounds Drive Bergmannian Clines in Nightjars - Aaron A. Skinner; Alicia M. Korpach; Susanne Åkesson; Marja H. Bakermans; Erin M. Bayne; Thomas J. Benson; Giovanni Boano; R. Mark Brigham; Simon S. Christiansen; Greg J. Conway; Christina M. Davy; Ruben Evens; et al. (Journal of Biogeography, 2025)
Aim To evaluate (1) whether three migratory nightjar species (Family Caprimulgidae) adhere to Bergmann's rule, (2) whether environmental factors on the breeding or wintering grounds determine body size, and (3) which mechanistic hypotheses best explain Bergmannian patterns in body size. Location North and South America; Europe and Africa. Taxon Eastern whip‐poor‐will ( Antrostomus vociferus ), Common nighthawk ( Chordeiles minor ) and European nightjar ( Caprimulgus europaeus ). Methods We used GPS tracking and morphometric data to assess competing hypotheses explaining variation in body size for each species, based on their breeding ( n = 3388) and wintering ( n = 189) locations. Results All three species exhibited Bergmannian patterns in body size, providing the first evidence that nightjars conform to Bergmann's rule despite adaptations to severe environmental conditions. Environmental and geographic variables at breeding sites were stronger predictors of body size than wintering‐site variables. Although we found partial support for Bergmann's temperature regulation hypothesis, geographic variables, rather than specific environmental factors, emerged as the strongest predictors of body size variation. Main Conclusions Latitude and longitude correlated strongly with environmental variables and migratory distance; thus, these geographical variables likely encompass many factors that influence body size in nightjars. The present study is among the first to use tracking data from individual birds to understand how environmental pressures across the annual cycle are related to body size. Our findings highlight the critical role of geographic breeding‐ground factors in shaping Bergmannian patterns, offering robust evidence to support nearly two centuries of research since Bergmann's rule was first described in 1847.

Selection on genome‐wide gene expression plasticity of rice in wet and dry field environments - Elena Hamann; Simon C. Groen; Taryn S. Dunivant; Irina Ćalić; Colleen Cochran; Rachel Konshok; Michael D. Purugganan; Steven J. Franks (Molecular Ecology, 2025)
Gene expression can be highly plastic in response to environmental variation. However, we know little about how expression plasticity is shaped by natural selection and evolves in wild and domesticated species. We used genotypic selection analysis to characterize selection on drought‐induced plasticity of over 7,500 leaf transcripts of 118 rice accessions (genotypes) from different environmental conditions grown in a field experiment. Gene expression plasticity was neutral for most gradually plastic transcripts, but transcripts with discrete patterns of expression showed stronger selection on expression plasticity. Whether plasticity was adaptive and co‐gradient or maladaptive and counter‐gradient varied among varietal groups. No transcripts that experienced selection for plasticity across environments showed selection against plasticity within environments, indicating a lack of evidence for costs of adaptive plasticity that may constrain its evolution. Selection on expression plasticity was influenced by degree of plasticity, transcript length and gene body methylation. We observed positive selection on plasticity of co‐expression modules containing transcripts involved in photosynthesis, translation and responsiveness to abiotic stress. Taken together, these results indicate that patterns of selection on expression plasticity were context‐dependent and likely associated with environmental conditions of varietal groups, but that the evolution of adaptive plasticity would likely not be constrained by opposing patterns of selection on plasticity within compared to across environments. These results offer a genome‐wide view of patterns of selection and ecological constraints on gene expression plasticity and provide insights into the interplay between plastic and evolutionary responses to drought at the molecular level.

Polar ectotherms more vulnerable to warming than expected - Simon Bahrndorff; Peter Convey; Steven L. Chown; Jesper Givskov Sørensen (Trends in Ecology & Evolution, 2025)

Magnesian-suite volcanism and ancient crust building on the Moon 4.25 billion years ago - Christopher Yen; Cécile Deligny; Bradley Jolliff; Alexander Nemchin; Paul Carpenter; Martin Whitehouse; Renaud Merle; Ryan Ogliore; Jeremy Kent; Ryan Zeigler; Juliane Gross; Scott Eckley; et al. (Earth and Planetary Science Letters, 2025)

Diurnal and seasonal dynamics of regional CO2 drawdown at Harvard Forest: Integrating remote sensing and modeling perspectives - Yang Li; Ethan Manninen; Jonathan E. Franklin; Elaine Gottlieb; Shannon Lindsey; Joshua Simon Benmergui; Maryann Sargent; Apisada Chulakadabba; Taylor Jones; Ian Smith; Lucy R. Hutyra; Jia Chen; et al. (Science of The Total Environment, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

A simple model to represent damage and fracturing in rock salt caused by heating and subsequent cooling: Understanding brine inflow data from the Brine Availability Test in Salt (BATS) - Claire Watson; Steven Benbow; Alexander Bond; Simon Norris; Sam Parsons (Geomechanics for Energy and the Environment, 2025)

Comparative population genomics of manta rays has global implications for management - Emily Humble; Jane Hosegood; Gary Carvalho; Mark de Bruyn; Simon Creer; Guy M. W. Stevens; Amelia Armstrong; Ramon Bonfil; Mark Deakos; Daniel Fernando; Niv Froman; Lauren R. Peel; et al. (Molecular Ecology, 2025)
Understanding population connectivity and genetic diversity is of fundamental importance to conservation. However, in globally threatened marine megafauna, challenges remain due to their elusive nature and wide‐ranging distributions. As overexploitation continues to threaten biodiversity across the globe, such knowledge gaps compromise both the suitability and effectiveness of management actions. Here, we use a comparative framework to investigate genetic differentiation and diversity of manta rays, one of the most iconic yet vulnerable groups of elasmobranchs on the planet. Despite their recent divergence, we show how oceanic manta rays ( Mobula birostris ) display significantly higher heterozygosity than reef manta rays ( Mobula alfredi ) and that M. birostris populations display higher connectivity worldwide. Through inferring modes of colonization, we reveal how both contemporary and historical forces have likely influenced these patterns, with important implications for population management. Our findings highlight the potential for fisheries to disrupt population dynamics at both local and global scales and therefore have direct relevance for international conservation of marine species.

Orthopteran Neo‐Sex Chromosomes Reveal Dynamics of Recombination Suppression and Evolution of Supergenes - Suvratha Jayaprasad; Valentina Peona; Simon J. Ellerstrand; Roberto Rossini; Ignas Bunikis; Olga V. Pettersson; Remi‐André Olsen; Carl‐Johan Rubin; Elisabet Einarsdottir; Franziska Bonath; Tessa M. Bradford; Steven J. B. Cooper; et al. (Molecular Ecology, 2024)
The early evolution of sex chromosomes has remained obscure for more than a century. The Vandiemenella viatica species group of morabine grasshoppers is highly suited for studying the early stages of sex chromosome divergence and degeneration of the Y chromosome. This stems from the fact that neo‐XY sex chromosomes have independently evolved multiple times by X‐autosome fusions with different autosomes. Here, we generated new chromosome‐level assemblies for two chromosomal races representing karyotypes with and without neo‐sex chromosomes (P24XY and P24X0), and sequence data of a third chromosomal race with a different neo‐XY chromosome system (P25XY). Interestingly, these two neo‐XY chromosomal races are formed by different X‐autosome fusions (involving chr1 and chrB, respectively), and we found that both neo‐Y chromosomes have partly ceased to recombine with their neo‐X counterpart. We show that the neo‐XY chromosomes have diverged through accumulation of SNPs and structural mutations, and that many neo‐Y‐linked genes have degenerated since recombination ceased. However, the non‐recombining regions of neo‐Y chromosomes host non‐degenerated genes crucial for sex determination, such as sex‐lethal and transformer , alongside genes associated with spermatogenesis, fertility, and reproduction, illustrating their integrative role as a masculinizing supergene. Contrary to expectations, the neo‐Y chromosomes showed (slightly) lower density of transposable elements (TEs) compared to other genomic regions. The study reveals the unique dynamics of young sex chromosomes, with evolution of recombination suppression and pronounced decay of (some) neo‐sex chromosome genes, and provides a compelling case illustrating how chromosomal fusions and post‐fusion mutational processes contribute to the evolution of supergenes.

Extracting an accurate river network: Stream burning re-revisited - Qiuyang Chen; Simon M. Mudd; Mikael Attal; Steven Hancock (Remote Sensing of Environment, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Synthesis of results for Brine Availability Test in Salt (BATS) DECOVALEX-2023 Task E - Kristopher L. Kuhlman; Jeroen Bartol; Steven J. Benbow; Michelle Bourret; Oliver Czaikowski; Eric Guiltinan; Kyra Jantschik; Richard Jayne; Simon Norris; Jonny Rutqvist; Hua Shao; Philip H. Stauffer; et al. (Geomechanics for Energy and the Environment, 2024)

Synthesizing the spatial functionality of contemporary stock assessment software to identify future needs for next generation assessment platforms - Aaron M. Berger; Caren Barceló; Daniel R. Goethel; Simon D. Hoyle; Patrick D. Lynch; Jeremy McKenzie; Alistair Dunn; André E. Punt; Richard D. Methot; John Hampton; Clay E. Porch; Richard McGarvey; et al. (Fisheries Research, 2024)

Trigeneration based on the pyrolysis of rural waste in India: Environmental impact, economic feasibility and business model innovation - Simon Ascher; Jillian Gordon; Ivano Bongiovanni; Ian Watson; Kristinn Hermannsson; Steven Gillespie; Supravat Sarangi; Bauyrzhan Biakhmetov; Preeti Chaturvedi Bhargava; Thallada Bhaskar; Bhavya B. Krishna; Ashok Pandey; et al. (Science of The Total Environment, 2024)

Aqueous remote loading of model cationic peptides in uncapped poly(lactide-co-glycolide) microspheres for long-term controlled release - Desheng Liang; Simon Frank; Steven P. Schwendeman (Drug Delivery and Translational Research, 2024)

Feeding and biological differences induce wide variation in legacy persistent organic pollutant concentrations among toothed whales and polar bear in the Arctic - Adam F. Pedersen; Rune Dietz; Christian Sonne; Robert J. Letcher; Anna M. Roos; Malene Simon; Aqqalu Rosing-Asvid; Steven H. Ferguson; Melissa A. McKinney (Science of The Total Environment, 2024)

Grazing management for soil carbon in Australia: A review - Sarah E. McDonald; Warwick Badgery; Simon Clarendon; Susan Orgill; Katrina Sinclair; Rachelle Meyer; Dominique Bowen Butchart; Richard Eckard; David Rowlings; Peter Grace; Natalie Doran-Browne; Steven Harden; et al. (Journal of Environmental Management, 2023)

Aquaculture governance: five engagement arenas for sustainability transformation - Stefan Partelow; Furqan Asif; Christophe Béné; Simon Bush; Aisa O Manlosa; Ben Nagel; Achim Schlüter; Vishnumurthy M Chadag; Afrina Choudhury; Steven M Cole; Richard S Cottrell; Stefan Gelcich; et al. (Current Opinion in Environmental Sustainability, 2023)

Global responses to the COVID-19 pandemic by recreational anglers: considerations for developing more resilient and sustainable fisheries - J. Robert Britton; Adrian C. Pinder; Josep Alós; Robert Arlinghaus; Andy J. Danylchuk; Wendy Edwards; Kátia M. F. Freire; Casper Gundelund; Kieran Hyder; Ivan Jarić; Robert Lennox; Wolf-Christian Lewin; et al. (Reviews in Fish Biology and Fisheries, 2023)
The global COVID-19 pandemic resulted in many jurisdictions implementing orders restricting the movements of people to inhibit virus transmission, with recreational angling often either not permitted or access to fisheries and/or related infrastructure being prevented. Following the lifting of restrictions, initial angler surveys and licence sales suggested increased participation and effort, and altered angler demographics, but with evidence remaining limited. Here, we overcome this evidence gap by identifying temporal changes in angling interest, licence sales, and angling effort in world regions by comparing data in the ‘pre-pandemic’ (up to and including 2019); ‘acute pandemic’ (2020) and ‘COVID-acclimated’ (2021) periods. We then identified how changes can inform the development of more resilient and sustainable recreational fisheries. Interest in angling (measured here as angling-related internet search term volumes) increased substantially in all regions during 2020. Patterns in licence sales revealed marked increases in some countries during 2020 but not in others. Where licence sales increased, this was rarely sustained in 2021; where there were declines, these related to fewer tourist anglers due to movement restrictions. Data from most countries indicated a younger demographic of people who participated in angling in 2020, including in urban areas, but this was not sustained in 2021. These short-lived changes in recreational angling indicate efforts to retain younger anglers could increase overall participation levels, where efforts can target education in appropriate angling practices and create more urban angling opportunities. These efforts would then provide recreational fisheries with greater resilience to cope with future global crises, including facilitating the ability of people to access angling opportunities during periods of high societal stress.

Combining dynamic material flow analysis and life cycle assessment to evaluate environmental benefits of recycling – A case study for direct and hydrometallurgical closed-loop recycling of electric vehicle battery systems - Sonja Rosenberg; Leonard Kurz; Sandra Huster; Steven Wehrstein; Steffen Kiemel; Frank Schultmann; Frederik Reichert; Ralf Wörner; Simon Glöser-Chahoud (Resources, Conservation and Recycling, 2023)

Bridging the gap for ice–ocean–ecosystem processes: integrated observing system for the Ross Sea-far East Antarctic Region - Petra Heil; Craig Stevens; Won Sang Lee; Clare Eayrs; Hyoung Chul Shin; Simon P. Alexander; Wolfgang Rack (Frontiers in Marine Science, 2023)
Our understanding of cross-disciplinary connections for Antarctica’s role in the Earth system remains incomplete, especially around its coastal margins. The focus here is on sea-ice, oceanic, and atmospheric drivers in the joint Ross Sea-far East Antarctic Region (RSfEAR)—one which spans a large longitudinal range and connects a number of ice shelves and polynyas promoting sea-ice growth and underpinning a diverse and rich ecosystem. Here, we present a minireview of recent case studies and how these inform the design for a future integrated ocean–sea ice–atmosphere observing system. The review is built around five themes: i) regional setting, ii) recent studies in the region and current strategies, iii) gap analysis, iv) future observing system design, and v) wider implications for stakeholders.

Chronology of alkali anorthosite 14304 clast “b” records basin forming impact at ∼3.95 Ga - Thomas S. Kruijer; Lars E. Borg; William S. Cassata; Josh Wimpenny; Greg A. Brennecka; Charles K. Shearer; Steven B. Simon (Geochimica et Cosmochimica Acta, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Analysis of Uranium Sorption in a Laboratory Column Experiment Using a Reactive Transport and Surface Complexation Model - Yousef Baqer; Steven Thornton; Douglas I. Stewart; Simon Norris; XiaoHui Chen (Transport in Porous Media, 2023)
The transport and retardation of radioactive elements in hyper-alkaline conditions of radioactive waste repositories is a challenging field that is still poorly understood. In this study, the transport and attenuation of uranium in a column experiment was modelled by considering kinetic reactions, advection–dispersion and chemical/physical retardation processes. The modelling was first performed for three alluvium samples from Yucca Mountain in circumneutral pH to moderately alkaline conditions. Sorption of uranyl ( $${UO}_{2}^{2+} (U_{VI})$$ UO 2 2 + ( U VI ) ) was found to strongly depend on the surface complexation model assumed, with no significant removal of $${U}_{VI}$$ U VI by precipitation or ion exchange process. The surface/edge site reaction of Al-hydroxyl group in kaolinite was shown to have a high affinity for uranyl adsorption, while the hydrous ferric oxide edge on hematite adsorbed most of the uranyl ions. The model was then used to interpret uranium transport in a laboratory column filled with Hollington sandstone under hyper-alkaline (pH 13) conditions. The simulation results show that uranium adsorption on the Al-hydroxyl edge of kaolinite exceeds adsorption by the calcium silicate hydrate phase. This result may reflect the lack of surface complexation parameters for calcium silicate hydrate minerals. Hence, further studies are required in the field of surface complexation reactions for calcium silicate hydrate phases. Graphical Abstract

Stone artefacts on the seabed at a submerged freshwater spring confirm a drowned cultural landscape in Murujuga, Western Australia - Jonathan Benjamin; Michael O'Leary; John McCarthy; Wendy Reynen; Chelsea Wiseman; Jerem Leach; Simon Bobeldyk; Justine Buchler; Philippe Kermeen; Michelle Langley; Adam Black; Hiro Yoshida; et al. (Quaternary Science Reviews, 2023)

Exposure assessment for repeated sub-concussive head impacts in soccer: The HEalth and Ageing Data IN the Game of football (HEADING) study - Ioannis Basinas; Damien M. McElvenny; Finley Brooker; Steven Robertson; Yvonne van Hoecke; Simon Kemp; Neil Pearce; Valentina Gallo; John W. Cherrie (International Journal of Hygiene and Environmental Health, 2023)

Middle Palaeolithic occupation of the southern North Sea Basin: evidence from the Sandscaping sediments emplaced on the beach between Bacton and Walcott, Norfolk, UK - Rob Davis; Nick Ashton; Rachel Bynoe; John Craven; Rob Ferguson; Ian Gardner; Tim Grimmer; Claire Harris; Marcus Hatch; Colin Johnson; Joanne Leonard; Simon Lewis; et al. (Journal of Quaternary Science, 2023)
During the summer of 2019, the Bacton to Walcott Coastal Management Scheme involved the emplacement on to the foreshore of 1.8 million cubic metres of sand and gravel dredged from the submerged sediments of the Palaeo‐Yare in the southern North Sea 11 km off Great Yarmouth. During the following 2‐year period, an active group of collectors identified Palaeolithic artefacts eroding from these sediments, including Levallois cores and flakes, and cordiform handaxes. In this paper, we present an analysis of the lithic artefacts, and consider the relationships between the different elements of the assemblage. We discuss its significance in the context of the Middle Palaeolithic record of northwest Europe and the light it shines on the human occupation of the submerged landscape of the southern North Sea during the later Middle Pleistocene. Interrogation of beach survey data shows the reworking of these sediments to the southeast towards Happisburgh where archaeologically significant exposures of the Cromer Forest‐bed Formation are located. The implications of the introduction of a Middle Palaeolithic assemblage to this stretch of the North Norfolk Coast are considered, highlighting the importance of continuing dialogue between researchers, local authorities and local communities for capturing information and monitoring this critical Palaeolithic resource.

Evaluating the importance of accurate sex ratios on egg deposition targets and conservation limit compliance for Atlantic salmon ( Salmo salar L.) in the River Tamar, south‐west England - R. Andrew King; Simon Toms; Jamie R. Stevens (Fisheries Management and Ecology, 2023)
Effective management of Atlantic salmon requires a suite of metrics that are fed into stock assessment models to assess stock compliance within individual rivers in relation to estimated conservation limits. Key among metrics required to assess compliance are the number of adult female spawners within each adult sea age class and their corresponding egg deposition rates. Owing to the current need to conserve salmon stocks, adult sex ratios used to calculate egg deposition estimates often depend on data derived from historic lethal sampling. Using non‐invasive sampling and an accurate genetic sex test, we determined the proportion of female fish in two adult life history stages (one sea winter and two sea winter) of Atlantic salmon from the River Tamar, an Environment Agency (England) Monitored River. Our results suggested that phenotypic‐based sexing of Tamar salmon was unreliable, especially for early run fish and that the proportion of female salmon has been under‐estimated, thereby leading to consistent under‐estimation of egg deposition rates.

Insights into Salt Marsh Plant Community Distributions Through Computer Vision and Structural Equation Modeling - Jacob Simon; Brian Hopkinson; Steven Pennings (Estuaries and Coasts, 2023)

Estimating the 3D structure of the Enceladus ice shell from Flexural and Crary waves using seismic simulations - Angela G. Marusiak; Saikiran Tharimena; Mark P. Panning; Steven D. Vance; Christian Boehm; Simon Stähler; Martin Van Driel (Earth and Planetary Science Letters, 2023)

The description, distribution and habitat of wild banana species in northern Viet Nam - Tuong Dang Vu; Dang Toan Vu; Steven B. Janssens; Edmond De Langhe; Loan Thi Le; Simon Kallow; Arne Mertens; Thi Thu Hien Vu; Thanh Tuan Nguyen (Genetic Resources and Crop Evolution, 2023)
Northern Viet Nam displays a remarkable diversity of wild bananas ( Musa L.) , including the species from which the majority of cultivated bananas derive. The taxonomy and exact distribution of these wild bananas are however not well known, limiting their conservation and use. In the present study, we describe the morphology, ecology, and phytogeography of the 6 Musa species that were collected between 2016 and 2019 in northern Viet Nam: Musa acuminata Colla, M. balbisiana Colla, M. itinerans Cheesman, M. haekkinenii N.S.Ly & Haev, M. lutea R.V.Valmayor, L.D.Danh and Hakkinen and M. paracoccinea A.Z.Liu and D.Z.Li:. Of these, M. itinerans was the species with the most widespread distribution range, occurring as large mats in various habitats between 136 and 1331 m, whereas M. acuminata was found between 136 and 989 m and M. balbisiana was between 108 and 981 m. Furthermore, M. lutea, M. paracoccinea and M. haekkinenii were distributed in open areas with low competition for light, between 80 and 800 m. These latter three species have the potential to become ornamental plants, being characterized by bright and colourful upright inflorescences. The data presented here will help in providing a valuable contribution to the conservation and use of the wild bananas in northern Viet Nam.

Distribution of the reef manta ray Mobula alfredi and the oceanic manta ray Mobula birostris in the Philippines: a collaborative effort for conservation - Joshua Rambahiniarison; Ariana Agustines; Konstantinos Alexopoulos; Gonzalo Araujo; Asia O. Armstrong; Shannon Arnold; Aldrin Barruga; Titus Cañete; Segundo Conales; Kymry Delijero; Nonie P. Enolva; Anna L. Flam; et al. (Journal of Fish Biology, 2023)
Little is known about manta ray population size, structure and connectivity in the Philippines. In collaboration with dive operators, non‐governmental organizations and authorities, sightings of manta rays were collated into a single national database. Using in‐water photographs and videos gathered through citizen science and dedicated research efforts, this study compiled sightings between 2004 and 2020, showing 22 separate sites throughout the archipelago with manta rays present. A total of 392 individual reef manta rays ( Mobula alfredi ) and 107 oceanic manta rays ( Mobula birostris ) were identified from the collected footage. Four specific sites in the provinces of Masbate and Palawan together hosted 89% of all identified individuals and accounted for 95% of sightings, highlighting these areas are key aggregation sites. This study also reports the movements of M. birostris within the Philippines, based on photo‐identification of three individuals moving 150 km between Cebu and Masbate. Despite the growing number of recreational divers in Daanbantayan and San Jacinto, an 80% decline in M. birostris sightings was observed at these sites. To ensure effective future conservation, it is recommended that efforts focus on the identification and protection of manta ray hotspots and migratory corridors, the creation of a sustainable tourism framework and, most important, the implementation of mitigation strategies to reduce fisheries interactions.

Phylogeography and conservation gaps of Musa balbisiana Colla genetic diversity revealed by microsatellite markers - Arne Mertens; Yves Bawin; Samuel Vanden Abeele; Simon Kallow; Rony Swennen; Dang Toan Vu; Tuong Dang Vu; Ho Thi Minh; Bart Panis; Filip Vandelook; Steven B. Janssens (Genetic Resources and Crop Evolution, 2022)
Collection and storage of crop wild relative (CWR) germplasm is crucial for preserving species genetic diversity and crop improvement. Nevertheless, much of the genetic variation of CWRs is absent in ex situ collections and detailed passport data are often lacking. Here, we focussed on Musa balbisiana, one of the two main progenitor species of many banana cultivars. We investigated the genetic structure of M. balbisiana across its distribution range using microsatellite markers. Accessions stored at the International Musa Germplasm Transit Centre (ITC) ex situ collection were compared with plant material collected from multiple countries and home gardens from Vietnam. Genetic structure analyses revealed that accessions could be divided into three main clusters. Vietnamese and Chinese populations were assigned to a first and second cluster respectively. A third cluster consisted of ITC and home garden accessions. Samples from Papua New Guinea were allocated to the cluster with Chinese populations but were assigned to a separate fourth cluster if the number of allowed clusters was set higher. Only one ITC accession grouped with native M. balbisiana populations and one group of ITC accessions was nearly genetically identical to home garden samples. This questioned their wild status, including accessions used as reference for wild M. balbisiana . Moreover, most ITC accessions and home garden samples were genetically distinct from wild populations. Our results highlight that additional germplasm should be collected from the native distribution range, especially from Northeast India, Myanmar, China, and the Philippines and stored for ex situ conservation at the ITC. The lack of passport data for many M. balbisiana accessions also complicates the interpretation of genetic information in relation to cultivation and historical dispersal routes.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Changes in tree drought sensitivity provided early warning signals to the California drought and forest mortality event - Rachel M. Keen; Steven L. Voelker; S.‐Y. Simon Wang; Barbara J. Bentz; Michael L. Goulden; Cody R. Dangerfield; Charlotte C. Reed; Sharon M. Hood; Adam Z. Csank; Todd E. Dawson; Andrew G. Merschel; Christopher J. Still (Global Change Biology, 2022)
Climate warming in recent decades has negatively impacted forest health in the western United States. Here, we report on potential early warning signals (EWS) for drought‐related mortality derived from measurements of tree‐ring growth (ring width index; RWI) and carbon isotope discrimination (∆ 13 C), primarily focused on ponderosa pine ( Pinus ponderosa ). Sampling was conducted in the southern Sierra Nevada Mountains, near the epicenter of drought severity and mortality associated with the 2012–2015 California drought and concurrent outbreak of western pine beetle ( Dendroctonus brevicomis ). At this site, we found that widespread mortality was presaged by five decades of increasing sensitivity (i.e., increased explained variation) of both tree growth and ∆ 13 C to Palmer Drought Severity Index (PDSI). We hypothesized that increasing sensitivity of tree growth and ∆ 13 C to hydroclimate constitute EWS that indicate an increased likelihood of widespread forest mortality caused by direct and indirect effects of drought. We then tested these EWS in additional ponderosa pine‐dominated forests that experienced varying mortality rates associated with the same California drought event. In general, drier sites showed increasing sensitivity of RWI to PDSI over the last century, as well as higher mortality following the California drought event compared to wetter sites. Two sites displayed evidence that thinning or fire events that reduced stand basal area effectively reversed the trend of increasing hydroclimate sensitivity. These comparisons indicate that reducing competition for soil water and/or decreasing bark beetle host tree density via forest management—particularly in drier regions—may buffer these forests against drought stress and associated mortality risk. EWS such as these could provide land managers more time to mitigate the extent or severity of forest mortality in advance of droughts. Substantial efforts at deploying additional dendrochronological research in concert with remote sensing and forest modeling will aid in forecasting of forest responses to continued climate warming.

The ten steps to responsible Inland fisheries in practice: reflections from diverse regional case studies around the globe - Steven J. Cooke; Elizabeth Nyboer; Abigail Bennett; Abigail J. Lynch; Dana M. Infante; Ian G. Cowx; T. Douglas Beard; Devin Bartley; Craig P. Paukert; Andrea J. Reid; Simon Funge-Smith; Edith Gondwe; et al. (Reviews in Fish Biology and Fisheries, 2021)

Ambrein: a minor, but common constituent of mammalian faeces? - Steven J. Rowland; Paul A. Sutton; Barbara von der Lühe; John K. Volkman; Christopher H. Vane; Simon N. Ingram; Charlotte Dunn; Diane Claridge (Natural Product Research, 2021)

Functional biogeography of Neotropical moist forests: Trait–climate relationships and assembly patterns of tree communities - Bruno X. Pinho; Marcelo Tabarelli; Cajo J. F. ter Braak; S. Joseph Wright; Víctor Arroyo‐Rodríguez; Maíra Benchimol; Bettina M. J. Engelbrecht; Simon Pierce; Peter Hietz; Bráulio A. Santos; Carlos A. Peres; Sandra C. Müller; et al. (Global Ecology and Biogeography, 2021)
Aim Here we examine the functional profile of regional tree species pools across the latitudinal distribution of Neotropical moist forests, and test trait–climate relationships among local communities. We expected opportunistic strategies (acquisitive traits, small seeds) to be overrepresented in species pools further from the equator, but also in terms of abundance in local communities in currently wetter, warmer and more seasonal climates. Location Neotropics. Time period Recent. Major taxa studied Trees. Methods We obtained abundance data from 471 plots across nine Neotropical regions, including c . 100,000 trees of 3,417 species, in addition to six functional traits. We compared occurrence‐based trait distributions among regional species pools, and evaluated single trait–climate relationships across local communities using community abundance‐weighted means (CWMs). Multivariate trait–climate relationships were assessed by a double‐constrained correspondence analysis that tests both how CWMs relate to climate and how species distributions, parameterized by niche centroids in climate space, relate to their traits. Results Regional species pools were undistinguished in functional terms, but opportunistic strategies dominated local communities further from the equator, particularly in the Northern Hemisphere. Climate explained up to 57% of the variation in CWM traits, with increasing prevalence of lower‐statured, light‐wooded and softer‐leaved species bearing smaller seeds in more seasonal, wetter and warmer climates. Species distributions were significantly but weakly related to functional traits. Main conclusions Neotropical moist forest regions share similar sets of functional strategies, from which local assembly processes, driven by current climatic conditions, select for species with different functional strategies. We can thus expect functional responses to climate change driven by changes in relative abundances of species already present regionally. Particularly, equatorial forests holding the most conservative traits and large seeds are likely to experience the most severe changes if climate change triggers the proliferation of opportunistic tree species.

Maximum likelihood inference for the band-read error model for capture-recapture data with misidentification - Wei Zhang; Steven J. Price; Simon J. Bonner (Environmental and Ecological Statistics, 2021)

Rapid evolutionary changes in gene expression in response to climate fluctuations - Elena Hamann; Christopher S. Pauli; Zoé Joly‐Lopez; Simon C. Groen; Joshua S. Rest; Nolan C. Kane; Michael D. Purugganan; Steven J. Franks (Molecular Ecology, 2021)
There is now abundant evidence of rapid evolution in natural populations, but the genetic mechanisms of these changes remain unclear. One possible route to rapid evolution is through changes in the expression of genes that influence traits under selection. We examined contemporary evolutionary gene expression changes in plant populations responding to environmental fluctuations. We compared genome‐wide gene expression, using RNA‐seq, in two populations of Brassica rapa collected over four time points between 1997 and 2014, during which precipitation in southern California fluctuated dramatically and phenotypic and genotypic changes occurred. By combining transcriptome profiling with the resurrection approach, we directly examined evolutionary changes in gene expression over time. For both populations, we found a substantial number of differentially expressed genes between generations, indicating rapid evolution in the expression of many genes. Using existing gene annotations, we found that many changes occurred in genes involved in regulating stress responses and flowering time. These appeared related to the fluctuations in precipitation and were potentially adaptive. However, the evolutionary changes in gene expression differed across generations within and between populations, indicating largely independent evolutionary trajectories across populations and over time. Our study provides strong evidence for rapid evolution in gene expression, and indicates that changes in gene expression can be one mechanism of rapid evolutionary responses to selection episodes. This study also illustrates that combining resurrection studies with transcriptomics is a powerful approach for investigating evolutionary changes at the gene regulatory level, and will provide new insights into the genetic basis of contemporary evolution.

Large uncertainties in future biome changes in Africa call for flexible climate adaptation strategies - Carola Martens; Thomas Hickler; Claire Davis‐Reddy; Francois Engelbrecht; Steven I. Higgins; Graham P. von Maltitz; Guy F. Midgley; Mirjam Pfeiffer; Simon Scheiter (Global Change Biology, 2021)
Anthropogenic climate change is expected to impact ecosystem structure, biodiversity and ecosystem services in Africa profoundly. We used the adaptive Dynamic Global Vegetation Model (aDGVM), which was originally developed and tested for Africa, to quantify sources of uncertainties in simulated African potential natural vegetation towards the end of the 21st century. We forced the aDGVM with regionally downscaled high‐resolution climate scenarios based on an ensemble of six general circulation models (GCMs) under two representative concentration pathways (RCPs 4.5 and 8.5). Our study assessed the direct effects of climate change and elevated CO 2 on vegetation change and its plant‐physiological drivers. Total increase in carbon in aboveground biomass in Africa until the end of the century was between 18% to 43% (RCP4.5) and 37% to 61% (RCP8.5) and was associated with woody encroachment into grasslands and increased woody cover in savannas. When direct effects of CO 2 on plants were omitted, woody encroachment was muted and carbon in aboveground vegetation changed between –8 to 11% (RCP 4.5) and –22 to –6% (RCP8.5). Simulated biome changes lacked consistent large‐scale geographical patterns of change across scenarios. In Ethiopia and the Sahara/Sahel transition zone, the biome changes forecast by the aDGVM were consistent across GCMs and RCPs. Direct effects from elevated CO 2 were associated with substantial increases in water use efficiency, primarily driven by photosynthesis enhancement, which may relieve soil moisture limitations to plant productivity. At the ecosystem level, interactions between fire and woody plant demography further promoted woody encroachment. We conclude that substantial future biome changes due to climate and CO 2 changes are likely across Africa. Because of the large uncertainties in future projections, adaptation strategies must be highly flexible. Focused research on CO 2 effects, and improved model representations of these effects will be necessary to reduce these uncertainties.

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Phylogenomics and species delimitation for effective conservation of manta and devil rays - Jane Hosegood; Emily Humble; Rob Ogden; Mark de Bruyn; Simon Creer; Guy M. W. Stevens; Mohammed Abudaya; Kim Bassos‐Hull; Ramon Bonfil; Daniel Fernando; Andrew D. Foote; Helen Hipperson; et al. (Molecular Ecology, 2020)
Practical biodiversity conservation relies on delineation of biologically meaningful units. Manta and devil rays (Mobulidae) are threatened worldwide, yet morphological similarities and a succession of recent taxonomic changes impede the development of an effective conservation strategy. Here, we generate genome‐wide single nucleotide polymorphism (SNP) data from a geographically and taxonomically representative set of manta and devil ray samples to reconstruct phylogenetic relationships and evaluate species boundaries under the general lineage concept. We show that nominal species units supported by alternative data sources constitute independently evolving lineages, and find robust evidence for a putative new species of manta ray in the Gulf of Mexico. Additionally, we uncover substantial incomplete lineage sorting indicating that rapid speciation together with standing variation in ancestral populations has driven phylogenetic uncertainty within Mobulidae. Finally, we detect cryptic diversity in geographically distinct populations, demonstrating that management below the species level may be warranted in certain species. Overall, our study provides a framework for molecular genetic species delimitation that is relevant to wide‐ranging taxa of conservation concern, and highlights the potential for genomic data to support effective management, conservation and law enforcement strategies.

Evaluating the potential of full‐waveform lidar for mapping pan‐tropical tree species richness - Suzanne M. Marselis; Katharine Abernethy; Alfonso Alonso; John Armston; Timothy R. Baker; Jean‐Francois Bastin; Jan Bogaert; Doreen S. Boyd; Pascal Boeckx; David F. R. P. Burslem; Robin Chazdon; David B. Clark; et al. (Global Ecology and Biogeography, 2020)
Aim Mapping tree species richness across the tropics is of great interest for effective conservation and biodiversity management. In this study, we evaluated the potential of full‐waveform lidar data for mapping tree species richness across the tropics by relating measurements of vertical canopy structure, as a proxy for the occupation of vertical niche space, to tree species richness. Location Tropics. Time period Present. Major taxa studied Trees. Methods First, we evaluated the characteristics of vertical canopy structure across 15 study sites using (simulated) large‐footprint full‐waveform lidar data (22 m diameter) and related these findings to in‐situ tree species information. Then, we developed structure–richness models at the local (within 25–50 ha plots), regional (biogeographical regions) and pan‐tropical scale at three spatial resolutions (1.0, 0.25 and 0.0625 ha) using Poisson regression. Results The results showed a weak structure–richness relationship at the local scale. At the regional scale (within a biogeographical region) a stronger relationship between canopy structure and tree species richness across different tropical forest types was found, for example across Central Africa and in South America [ R 2 ranging from .44–.56, root mean squared difference as a percentage of the mean (RMSD%) ranging between 23–61%]. Modelling the relationship pan‐tropically, across four continents, 39% of the variation in tree species richness could be explained with canopy structure alone ( R 2 = .39 and RMSD% = 43%, 0.25‐ha resolution). Main conclusions Our results may serve as a basis for the future development of a set of structure–richness models to map high resolution tree species richness using vertical canopy structure information from the Global Ecosystem Dynamics Investigation (GEDI). The value of this effort would be enhanced by access to a larger set of field reference data for all tropical regions. Future research could also support the use of GEDI data in frameworks using environmental and spectral information for modelling tree species richness across the tropics.

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Assessing the sublethal impacts of anthropogenic stressors on fish: An energy‐budget approach - Joseph W. Watson; Kieran Hyder; Robin Boyd; Robert Thorpe; Marc Simon Weltersbach; Keno Ferter; Steven J. Cooke; Shovonlal Roy; Richard M. Sibly (Fish and Fisheries, 2020)
Fish are increasingly exposed to anthropogenic stressors from human developments and activities such as agriculture, urbanization, pollution and fishing. Lethal impacts of these stressors have been studied but the potential sublethal impacts, such as behavioural changes or reduced growth and reproduction, have often been overlooked. Unlike mortality, sublethal impacts are broad and difficult to quantify experimentally. As a result, sublethal impacts are often ignored in regulatory frameworks and management decisions. Building on established fish bioenergetic models, we present a general method for using the population consequences of disturbance framework to investigate how stressors influence ecologically relevant life processes of fish. We partition impact into the initial energetic cost of attempts to escape from the stressor, followed by the energetic impacts of any injury or behavioural change, and their consequent effects on life processes. As a case study, we assess the sublethal effects of catch and release angling for the European sea bass ( Dicentrachus labrax , Moronidae ), a popular target species for recreational fishers. The energy budget model described is not intended to replace existing experimental approaches but does provide a simple way to account for sublethal impacts in assessment of the impact of recreational fisheries and aid development of robust management approaches. There is potential to apply our energy budget approach to investigate a broad range of stressors and cumulative impacts for many fish species while also using individual‐based models to estimate population‐level impacts.

Increased yield and CO 2 sequestration potential with the C 4 cereal Sorghum bicolor cultivated in basaltic rock dust‐amended agricultural soil - Mike E. Kelland; Peter W. Wade; Amy L. Lewis; Lyla L. Taylor; Binoy Sarkar; M. Grace Andrews; Mark R. Lomas; T. E. Anne Cotton; Simon J. Kemp; Rachael H. James; Christopher R. Pearce; Sue E. Hartley; et al. (Global Change Biology, 2020)
Land‐based enhanced rock weathering (ERW) is a biogeochemical carbon dioxide removal (CDR) strategy aiming to accelerate natural geological processes of carbon sequestration through application of crushed silicate rocks, such as basalt, to croplands and forested landscapes. However, the efficacy of the approach when undertaken with basalt, and its potential co‐benefits for agriculture, require experimental and field evaluation. Here we report that amending a UK clay‐loam agricultural soil with a high loading (10 kg/m 2 ) of relatively coarse‐grained crushed basalt significantly increased the yield (21 ± 9.4%, SE ) of the important C 4 cereal Sorghum bicolor under controlled environmental conditions, without accumulation of potentially toxic trace elements in the seeds. Yield increases resulted from the basalt treatment after 120 days without P‐ and K‐fertilizer addition. Shoot silicon concentrations also increased significantly (26 ± 5.4%, SE ), with potential benefits for crop resistance to biotic and abiotic stress. Elemental budgets indicate substantial release of base cations important for inorganic carbon removal and their accumulation mainly in the soil exchangeable pools. Geochemical reactive transport modelling, constrained by elemental budgets, indicated CO 2 sequestration rates of 2–4 t CO 2 /ha, 1–5 years after a single application of basaltic rock dust, including via newly formed soil carbonate minerals whose long‐term fate requires assessment through field trials. This represents an approximately fourfold increase in carbon capture compared to control plant–soil systems without basalt. Our results build support for ERW deployment as a CDR technique compatible with spreading basalt powder on acidic loamy soils common across millions of hectares of western European and North American agriculture.

Opportunities for agent‐based modelling in human dimensions of fisheries - Matthew G. Burgess; Ernesto Carrella; Michael Drexler; Robert L. Axtell; Richard M. Bailey; James R. Watson; Reniel B. Cabral; Michaela Clemence; Christopher Costello; Chris Dorsett; Steven D. Gaines; Emily S. Klein; et al. (Fish and Fisheries, 2020)
Models of human dimensions of fisheries are important to understanding and predicting how fishing industries respond to changes in marine ecosystems and management institutions. Advances in computation have made it possible to construct agent‐based models (ABMs)—which explicitly describe the behaviour of individual people, firms or vessels in order to understand and predict their aggregate behaviours. ABMs are widely used for both academic and applied purposes in many settings including finance, urban planning and the military, but are not yet mainstream in fisheries science and management, despite a growing literature. ABMs are well suited to understanding emergent consequences of fisher interactions, heterogeneity and bounded rationality, especially in complex ecological, social and institutional contexts. For these reasons, we argue that ABMs of human behaviour can contribute significantly to human dimensions of fisheries in three areas: (a) understanding interactions between multiple management institutions; (b) incorporating cognitive and behavioural sciences into fisheries science and practice; and (c) understanding and projecting the social consequences of management institutions. We provide simple examples illustrating the potential for ABMs in each of these areas, using conceptual (“toy”) versions of the POSEIDON model. We argue that salient strategic advances in these areas could pave the way for increased tactical use of ABMs in fishery management settings. We review common ABM development and application challenges, with the aim of providing guidance to beginning ABM developers and users studying human dimensions of fisheries.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Examining progress towards achieving the Ten Steps of the Rome Declaration on Responsible Inland Fisheries - Abigail J. Lynch; Devin M. Bartley; Thomas Douglas Beard; Ian G. Cowx; Simon Funge‐Smith; William W. Taylor; Steven J. Cooke (Fish and Fisheries, 2020)
Inland capture fisheries provide food for nearly a billion people and are important in the livelihoods of millions of households worldwide. Although there are limitations to evaluating many of the contributions made by inland capture fisheries, there is growing recognition by the international community that these services make critical contributions, most notably to food security and livelihoods in rural populations in those low‐income countries with extensive freshwater resources. With the increasing appreciation of the key role of inland fisheries to the health and well‐being of human populations globally, the Food and Agriculture Organization of the United Nations and Michigan State University convened the 2015 global conference, Freshwater, fish, and the future – cross‐sectoral approaches to sustain livelihoods, food security, and aquatic ecosystems . What emerged from the interactions between inland fisheries’ scientists, resource managers, policymakers and community representatives from across the world was a forward‐looking call to action culminating with the 2015 Rome Declaration “Ten Steps to Responsible Inland Fisheries” (FAO & MSU, Rome declaration on responsible inland fisheries: 5735E/1/06.16 ). Four years after this landmark conference and declaration, we seek to advance discussion on the “Ten Steps,” namely what successful implementation looks like, assess current examples of implementation, suggest potential signals of progress and provide some specific, indicative examples of progress for each step. While there are promising signs of progress, we conclude that there remains a strong need to galvanize momentum for sustained action to ensure that inland fish and fisheries are accounted for and incorporated into broader water resource management discussions and frameworks.

Linking scales and disciplines: an interdisciplinary cross-scale approach to supporting climate-relevant ecosystem management - Christian Berger; Mari Bieri; Karen Bradshaw; Christian Brümmer; Thomas Clemen; Thomas Hickler; Werner Leo Kutsch; Ulfia A. Lenfers; Carola Martens; Guy F. Midgley; Kanisios Mukwashi; Victor Odipo; et al. (Climatic Change, 2019)

Ocean Climate Observing Requirements in Support of Climate Research and Climate Information - Detlef Stammer; Annalisa Bracco; Krishna AchutaRao; Lisa Beal; Nathaniel L. Bindoff; Pascale Braconnot; Wenju Cai; Dake Chen; Matthew Collins; Gokhan Danabasoglu; Boris Dewitte; Riccardo Farneti; et al. (Frontiers in Marine Science, 2019)

Landscape patterns in top‐down control of decomposition: omnivory disrupts a tropical detrital‐based trophic cascade - Troy N. Simon; Andrew J. Binderup; Alex S. Flecker; James F. Gilliam; Michael C. Marshall; Steven A. Thomas; Joseph Travis; David N. Reznick; Catherine M. Pringle (Ecology, 2019)
Detrital‐based trophic cascades are often considered weak or absent in tropical stream ecosystems because of the prevalence of omnivorous macroconsumers and the dearth of leaf‐shredding insects. In this study, we isolate top‐down effects of three macroconsumer species on detrital processing in headwater streams draining Trinidad's northern mountains. We separated effects of different macroconsumers by experimentally manipulating their temporal access to isolated benthic habitat over the diel cycle. We found no evidence that omnivorous macroconsumers, including a freshwater crab ( Eudaniela garmani ) and guppy ( Poecilia reticulata ), increased leaf decomposition via consumption. By contrast, above a waterfall excluding guppies, the insectivorous killifish, Anablepsoides hartii , reduced the biomass of the leaf‐shredding insect Phylloicus hansoni 4‐fold, which consequently reduced leaf decomposition rates 1.6‐fold. This detrital cascade did not occur below the barrier waterfall, where omnivorous guppies join the assemblage and reduce killifish densities; here killifish had no significant effects on Phylloicus or decomposition rates. These patterns of detrital processing were also observed in upstream–downstream comparisons in a landscape study across paired reaches of six streams. Above waterfalls, where killifish were present, but guppies absent, leaf decomposition rates and Phylloicus biomass were 2.5‐ and ~35‐fold lower, respectively, compared to measurements below waterfalls. Moreover, the strength of top‐down control by killifish is reflected by the 20‐ and 5‐fold reductions in variability (± SE ) surrounding mean Phylloicus biomass and leaf decomposition rates in upstream relative to downstream reaches where no top‐down control was detected. Findings show a clear, detrital‐based trophic cascade among killifish, a leaf‐shredding insect, and leaf decomposition rates. Results also show how omnivorous guppies disrupt this cascade by depressing killifish densities, thereby releasing invertebrate shredders from predation, and significantly increasing decomposition rates. Moreover, this combination of direct and indirect trophic interactions drives patterns in decomposition rates in stream networks at a landscape scale, resulting in significantly lower rates of decomposition above vs. below barrier waterfalls. Our findings reveal that omnivory can result in significant indirect effects on a key ecosystem process, illustrating the importance of these hidden trophic pathways in detrital‐based systems and suggesting that resource control in tropical systems may be even more complex than previously envisioned.

African shrub distribution emerges via a trade‐off between height and sapwood conductivity - Camille Gaillard; Liam Langan; Mirjam Pfeiffer; Dushyant Kumar; Carola Martens; Steven I. Higgins; Simon Scheiter (Journal of Biogeography, 2018)
Aim Shrubs are multistemmed woody plants and are a successful growth form in many ecosystems globally. Ecosystems such as the Fynbos in South Africa or mediterranean shrublands are dominated by a dense shrub cover. In savannas, shrubs are a major vegetation component. Despite the importance of shrubs at the global scale, they are, in contrast to trees, often understudied both in empirical and modelling studies. We define shrub and tree strategies by a trade‐off between water uptake capacity and height growth, and aim to explore if this trade‐off allows us to explain shrub distribution. Location Sub‐Saharan Africa Methods We improve a dynamic vegetation model, the adaptive Dynamic Global Vegetation Model version 2 ( aDGVM 2), to simulate shrubs as multistemmed woody plants, based on a trade‐off between rapid height growth in single‐stemmed trees and efficient water uptake in multistemmed shrubs. Results We show that, in aDGVM 2, (a) the implemented trade‐off allows a multistemmed shrub strategy to emerge and is sufficient to simulate the broad distribution of shrubs in African savannas; (b) fire and aridity promote shrubs at the expense of trees and grasses; and (c) the presence of shrubs influences competitive interactions between grasses and woody vegetation. Main conclusion We provide a novel approach to simulate shrubs in a dynamic vegetation model. This approach enhances our understanding of the distribution of shrubs , but further work is required for arid and mediterranean shrublands. We conclude that introducing fundamental trade‐offs between growth forms into vegetation models can improve vegetation representation.

Further spectral and chromatographic studies of ambergris - Steven J. Rowland; Paul A. Sutton; Simon T. Belt; Vera Fitzsimmons-Thoss; Alan G. Scarlett (Natural Product Research, 2018)

Patterns of Z chromosome divergence among Heliconius species highlight the importance of historical demography - Steven M. Van Belleghem; Margarita Baquero; Riccardo Papa; Camilo Salazar; W. Owen McMillan; Brian A. Counterman; Chris D. Jiggins; Simon H. Martin (Molecular Ecology, 2018)
Sex chromosomes are disproportionately involved in reproductive isolation and adaptation. In support of such a “large‐X” effect, genome scans between recently diverged populations and species pairs often identify distinct patterns of divergence on the sex chromosome compared to autosomes. When measures of divergence between populations are higher on the sex chromosome compared to autosomes, such patterns could be interpreted as evidence for faster divergence on the sex chromosome, that is “faster‐X”, barriers to gene flow on the sex chromosome. However, demographic changes can strongly skew divergence estimates and are not always taken into consideration. We used 224 whole‐genome sequences representing 36 populations from two Heliconius butterfly clades ( H. erato and H. melpomene ) to explore patterns of Z chromosome divergence. We show that increased divergence compared to equilibrium expectations can in many cases be explained by demographic change. Among Heliconius erato populations, for instance, population size increase in the ancestral population can explain increased absolute divergence measures on the Z chromosome compared to the autosomes, as a result of increased ancestral Z chromosome genetic diversity. Nonetheless, we do identify increased divergence on the Z chromosome relative to the autosomes in parapatric or sympatric species comparisons that imply postzygotic reproductive barriers. Using simulations, we show that this is consistent with reduced gene flow on the Z chromosome, perhaps due to greater accumulation of incompatibilities. Our work demonstrates the importance of taking demography into account to interpret patterns of divergence on the Z chromosome, but nonetheless provides evidence to support the Z chromosome as a strong barrier to gene flow in incipient Heliconius butterfly species.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Novel Formulation Strategy to Improve the Feasibility of Amifostine Administration - Kavitha Ranganathan; Eric Simon; Jeremy Lynn; Alicia Snider; Yu Zhang; Noah Nelson; Alexis Donneys; Jose Rodriguez; Lauren Buchman; Dawn Reyna; Elke Lipka; Steven R. Buchman (Pharmaceutical Research, 2018)

Biogeographic history of subterranean isopods from groundwater calcrete islands in Western Australia - Mohammad Javidkar; Steven J. B. Cooper; William F. Humphreys; Rachael A. King; Simon Judd; Andrew D. Austin (Zoologica Scripta, 2018)
Groundwater calcretes in arid central Western Australia contain a diverse invertebrate groundwater fauna (stygofauna). Surveys have uncovered a diverse oniscidean isopod subterranean fauna above the water table (troglofauna), including species of a recently described genus Paraplatyarthrus . The aim of this study was to investigate the biogeographic history of Paraplatyarthrus and the timing of transitions from surface to subterranean habitats. Phylogenetic relationships among the isopod troglofauna from 11 groundwater calcretes along three palaeodrainage systems were assessed using one mitochondrial gene, cytochrome c oxidase subunit 1 ( COI ) , and two nuclear markers, lysyl‐ tRNA synthetase (Lys RS ) and 18S rRNA ( 18S ) genes. Phylogenetic analyses revealed multiple sister lineage relationships between troglophile and troglobite lineages and evidence for divergent mt DNA lineages within species, providing a range of nodes for dating evolutionary transitions from surface to subterranean habitats. Relaxed molecular clock analyses provided evidence that evolutionary transitions from surface to subterranean environments took place between 13.3 and 1.75 million years ago, coinciding with the onset of aridification of Australia from the late Tertiary. In cases where groundwater calcretes contained multiple species, the taxa were not closely related phylogenetically, suggesting that these calcretes were independently colonised by multiple ancestral species. The study further confirmed the role of late/post‐Miocene aridification as a key driver of the evolution of subterranean invertebrates in the calcrete islands of Western Australia, supporting the climatic relict hypothesis. Troglobites most likely evolved from the troglophile ancestors that were capable of dispersal among, and active colonisation of, calcretes.

Trade‐offs in triple‐bottom‐line outcomes when recovering fisheries - Christopher J Brown; Glenn Althor; Benjamin S Halpern; Md Sayed Iftekhar; Carissa J Klein; Simon Linke; Elizabeth C Pryde; Steven Schilizzi; James E M Watson; Becky Twohey; Hugh P Possingham (Fish and Fisheries, 2018)
Almost all environmental management comes at an economic cost that may not be borne equitably by all stakeholders. Here, we investigate how heterogeneity in catch and profits among fishers influences the trade‐off among the triple‐bottom‐line objectives of recovering a fish population, maximizing its economic value and distributing restrictions equitably across fishers. As a case‐study, we examine management reform of an ecologically and economically important coral reef fishery operating within the Great Barrier Reef Marine Park. Using a simulation model, we find that total profitability of the fishing industry is 40% lower if recovery plans are equitable when compared to the most economically efficient plan. However, efficient recovery plans were typically highly inequitable because they required some fishers to cease fishing. Equity was defined according to different norms, and the efficiency loss was greatest when catch losses were shared equally across fishers rather than in proportion to their historical catch. We then varied key social, economic and biological parameters to identify cases when equity and efficient recovery would trade‐off most strongly. Recovery plans could be both efficient and equitable when heterogeneity in fisher's catches and individual catch efficiencies was lower. If fishers were homogenous then equitable plans could have maximal economic efficiency. These results emphasize the importance of considering heterogeneity in individual fishers when designing recovery plans. Recovery plans that are inequitable may often fail to gain stakeholder support, so in fisheries with high heterogeneity we should temper our expectations for marked increases in profits.

Integrated ecological–economic fisheries models—Evaluation, review and challenges for implementation - J Rasmus Nielsen; Eric Thunberg; Daniel S Holland; Jorn O Schmidt; Elizabeth A Fulton; Francois Bastardie; Andre E Punt; Icarus Allen; Heleen Bartelings; Michel Bertignac; Eckhard Bethke; Sieme Bossier; et al. (Fish and Fisheries, 2018)
Marine ecosystems evolve under many interconnected and area‐specific pressures. To fulfil society's intensifying and diversifying needs while ensuring ecologically sustainable development, more effective marine spatial planning and broader‐scope management of marine resources is necessary. Integrated ecological–economic fisheries models ( IEEFM s) of marine systems are needed to evaluate impacts and sustainability of potential management actions and understand, and anticipate ecological, economic and social dynamics at a range of scales from local to national and regional. To make these models most effective, it is important to determine how model characteristics and methods of communicating results influence the model implementation, the nature of the advice that can be provided and the impact on decisions taken by managers. This article presents a global review and comparative evaluation of 35 IEEFM s applied to marine fisheries and marine ecosystem resources to identify the characteristics that determine their usefulness, effectiveness and implementation. The focus is on fully integrated models that allow for feedbacks between ecological and human processes although not all the models reviewed achieve that. Modellers must invest more time to make models user friendly and to participate in management fora where models and model results can be explained and discussed. Such involvement is beneficial to all parties, leading to improvement of mo‐dels and more effective implementation of advice, but demands substantial resources which must be built into the governance process. It takes time to develop effective processes for using IEEFM s requiring a long‐term commitment to integrating multidisciplinary modelling advice into management decision‐making.

iDNA at Sea: Recovery of Whale Shark (Rhincodon typus) Mitochondrial DNA Sequences from the Whale Shark Copepod (Pandarus rhincodonicus) Confirms Global Population Structure - Mark Meekan; Christopher M. Austin; Mun H. Tan; Nu-Wei V. Wei; Adam Miller; Simon J. Pierce; David Rowat; Guy Stevens; Tim K. Davies; Alessandro Ponzo; Han Ming Gan (Frontiers in Marine Science, 2017)

Impacts of sea-level rise on sediment microbial community structure and function in two New England salt marshes, USA - Matt R. Simon; Gregory P. Zogg; Steven E. Travis (Journal of Soils and Sediments, 2017)

The Influence of Legacy P on Lake Water Quality in a Midwestern Agricultural Watershed - Melissa Motew; Xi Chen; Eric G. Booth; Stephen R. Carpenter; Pavel Pinkas; Samuel C. Zipper; Steven P. Loheide; Simon D. Donner; Kai Tsuruta; Peter A. Vadas; Christopher J. Kucharik (Ecosystems, 2017)

Drivers of nitrogen transfer in stream food webs across continents - Beth C. Norman; Matt R. Whiles; Sarah M. Collins; Alexander S. Flecker; Steve K. Hamilton; Sherri L. Johnson; Emma J. Rosi; Linda R. Ashkenas; William B. Bowden; Chelsea L. Crenshaw; Todd Crowl; Walter K. Dodds; et al. (Ecology, 2017)
Studies of trophic‐level material and energy transfers are central to ecology. The use of isotopic tracers has now made it possible to measure trophic transfer efficiencies of important nutrients and to better understand how these materials move through food webs. We analyzed data from thirteen 15 N‐ammonium tracer addition experiments to quantify N transfer from basal resources to animals in headwater streams with varying physical, chemical, and biological features. N transfer efficiencies from primary uptake compartments (PUCs; heterotrophic microorganisms and primary producers) to primary consumers was lower (mean 11.5%, range 100%). Total N transferred (as a rate) was greater in streams with open compared to closed canopies and overall N transfer efficiency generally followed a similar pattern, although was not statistically significant. We used principal component analysis to condense a suite of site characteristics into two environmental components. Total N uptake rates among trophic levels were best predicted by the component that was correlated with latitude, DIN:SRP, GPP:ER, and percent canopy cover. N transfer efficiency did not respond consistently to environmental variables. Our results suggest that canopy cover influences N movement through stream food webs because light availability and primary production facilitate N transfer to higher trophic levels.

Climate‐biomes, pedo‐biomes or pyro‐biomes: which world view explains the tropical forest–savanna boundary in South America? - Liam Langan; Steven I. Higgins; Simon Scheiter (Journal of Biogeography, 2017)
Aim It remains poorly understood why the position of the forest–savanna biome boundary, in a domain defined by precipitation and temperature, differs in South America, Africa and Australia. Process based Dynamic Global Vegetation Models (DGVMs) are a valuable tool to investigate the determinants of vegetation distributions; however, many DGVMs fail to predict the spatial distribution or indeed presence of the South American savanna biome. Evidence suggests that fire plays a significant role in mediating forest–savanna biome boundaries; however, fire alone appears to be insufficient to predict these boundaries in South America. We hypothesize that interactions between precipitation, constraints on tree rooting depth and fire affect the probability of savanna occurrence and the position of the savanna–forest boundary. Location Tropical forest and savanna sites in Brazil and Venezuela north of 23 S. Methods We tested our hypotheses using a novel DGVM, aDGVM2, which allows plant trait spectra, constrained by trade‐offs between traits, to evolve in response to abiotic and biotic conditions. Plant hydraulics is represented by the cohesion–tension theory, this allowed us to explore how soil and plant hydraulics control biome distributions and plant traits. The resulting community trait distributions are emergent properties of model dynamics. Results We showed that across much of South America the biome state is not determined by climate alone. Interactions between plant rooting depth, fire and precipitation affected the probability of observing a given biome state and the emergent traits of plant communities. Simulations where plant rooting depth varied in space provided the best match to satellite derived biomass estimates and generated biome distributions that reproduced contemporary biome maps well. Main conclusions Our findings support the contention that areas where multiple vegetation states are possible are widespread and highlight the importance of considering the influence of fire and constraints on plant rooting depth for predicting biome boundaries.

Evaluation of UAVs as an underwater acoustics sensor deployment platform - Steven Lloyd; Paul Lepper; Simon Pomeroy (International Journal of Remote Sensing, 2017)

Climate adaptation of food value chains: the implications of varying consumer acceptance - Lilly Lim-Camacho; Anoma Ariyawardana; Gemma K. Lewis; Steven J. Crimp; Simon Somogyi; Brad Ridoutt; Stuart Mark Howden (Regional Environmental Change, 2017)

Where Does River Runoff Matter for Coastal Marine Conservation? - Alexa Fredston-Hermann; Christopher J. Brown; Simon Albert; Carissa J. Klein; Sangeeta Mangubhai; Joanna L. Nelson; Lida Teneva; Amelia Wenger; Steven D. Gaines; Benjamin S. Halpern (Frontiers in Marine Science, 2016)

Dynamic habitat corridors for marine predators; intensive use of a coastal channel by harbour seals is modulated by tidal currents - Gordon D. Hastie; Deborah J.F. Russell; Steven Benjamins; Simon Moss; Ben Wilson; Dave Thompson (Behavioral Ecology and Sociobiology, 2016)

A 2-Substituted 8-Hydroxyquinoline Stimulates Neural Stem Cell Proliferation by Modulating ROS Signalling - Cathryn L. Haigh; Carolin Tumpach; Steven J. Collins; Simon C. Drew (Cell Biochemistry and Biophysics, 2016)

Estimating the prevalence of hematological malignancies and precursor conditions using data from Haematological Malignancy Research Network (HMRN) - Jinlei Li; Alex Smith; Simon Crouch; Steven Oliver; Eve Roman (Cancer Causes & Control, 2016)

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

Reinforcing and neurochemical effects of the “bath salts” constituents 3,4-methylenedioxypyrovalerone (MDPV) and 3,4-methylenedioxy-N-methylcathinone (methylone) in male rats - Charles W. Schindler; Eric B. Thorndike; Steven R. Goldberg; Kurt R. Lehner; Nicholas V. Cozzi; Simon D. Brandt; Michael H. Baumann (Psychopharmacology, 2016)

Out of Antarctica: quaternary colonization of sub-Antarctic Marion Island by the limpet genus Nacella (Patellogastropoda: Nacellidae) - Claudio A. González-Wevar; Steven L. Chown; Simon Morley; Nestor Coria; Thomas Saucéde; Elie Poulin (Polar Biology, 2016)

Propagation of the Madden–Julian Oscillation and scale interaction with the diurnal cycle in a high-resolution GCM - Simon C. Peatman; Adrian J. Matthews; David P. Stevens (Climate Dynamics, 2015)

The role of the export of tropical moisture into midlatitudes for extreme precipitation events in the Mediterranean region - Simon O. Krichak; Joseph Barkan; Joseph S. Breitgand; Silvio Gualdi; Steven B. Feldstein (Theoretical and Applied Climatology, 2015)

Geographic and temporal dynamics of a global radiation and diversification in the killer whale - Phillip A. Morin; Kim M. Parsons; Frederick I. Archer; María C. Ávila‐Arcos; Lance G. Barrett‐Lennard; Luciano Dalla Rosa; Sebastián Duchêne; John W. Durban; Graeme M. Ellis; Steven H. Ferguson; John K. Ford; Michael J. Ford; et al. (Molecular Ecology, 2015)
Global climate change during the Late Pleistocene periodically encroached and then released habitat during the glacial cycles, causing range expansions and contractions in some species. These dynamics have played a major role in geographic radiations, diversification and speciation. We investigate these dynamics in the most widely distributed of marine mammals, the killer whale ( Orcinus orca ), using a global data set of over 450 samples. This marine top predator inhabits coastal and pelagic ecosystems ranging from the ice edge to the tropics, often exhibiting ecological, behavioural and morphological variation suggestive of local adaptation accompanied by reproductive isolation. Results suggest a rapid global radiation occurred over the last 350 000 years. Based on habitat models, we estimated there was only a 15% global contraction of core suitable habitat during the last glacial maximum, and the resources appeared to sustain a constant global effective female population size throughout the Late Pleistocene. Reconstruction of the ancestral phylogeography highlighted the high mobility of this species, identifying 22 strongly supported long‐range dispersal events including interoceanic and interhemispheric movement. Despite this propensity for geographic dispersal, the increased sampling of this study uncovered very few potential examples of ancestral dispersal among ecotypes. Concordance of nuclear and mitochondrial data further confirms genetic cohesiveness, with little or no current gene flow among sympatric ecotypes. Taken as a whole, our data suggest that the glacial cycles influenced local populations in different ways, with no clear global pattern, but with secondary contact among lineages following long‐range dispersal as a potential mechanism driving ecological diversification.

Combination paracetamol and ibuprofen for pain relief after oral surgery: a dose ranging study - Hartley C. Atkinson; John Currie; John Moodie; Simon Carson; Steven Evans; James P. Worthington; Leon J. Steenberg; Eileen Bisley; Chris Frampton (European Journal of Clinical Pharmacology, 2015)

Evolution of Stratocumulus Over Land: Comparison of Ground and Aircraft Observations with Numerical Weather Prediction Simulations - Simon R. Osborne; Steven J. Abel; Ian A. Boutle; Franco Marenco (Boundary-Layer Meteorology, 2014)

Teleconnection–extreme precipitation relationships over the Mediterranean region - Simon O. Krichak; Joseph S. Breitgand; Silvio Gualdi; Steven B. Feldstein (Theoretical and Applied Climatology, 2014)

The Role of Nitrogen Deposition in Widespread Plant Community Change Across Semi-natural Habitats - Chris D. Field; Nancy B. Dise; Richard J. Payne; Andrea J. Britton; Bridget A. Emmett; Rachel C. Helliwell; Steve Hughes; Laurence Jones; Steven Lees; Jonathan R. Leake; Ian D. Leith; Gareth K. Phoenix; et al. (Ecosystems, 2014)

Attracted to the enemy: Aedes aegypti prefers oviposition sites with predator-killed conspecifics - Daniel Albeny-Simões; Ebony G. Murrell; Simon L. Elliot; Mateus R. Andrade; Eraldo Lima; Steven A. Juliano; Evaldo F. Vilela (Oecologia, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

Surface Charges of the Membrane Crucially Affect Regulation of Na,K-ATPase by Phospholemman (FXYD1) - Erica Cirri; Corinna Kirchner; Simon Becker; Adriana Katz; Steven J. Karlish; Hans-Jürgen Apell (The Journal of Membrane Biology, 2013)

Vulnerability of population and transportation infrastructure at the east bank of Delaware Bay due to coastal flooding in sea-level rise conditions - Han Song Tang; Steven I-Jy Chien; Marouane Temimi; Cheryl Ann Blain; Qu Ke; Liuhui Zhao; Simon Kraatz (Natural Hazards, 2013)

Regime shifts in a social-ecological system - Steven J. Lade; Alessandro Tavoni; Simon A. Levin; Maja Schlüter (Theoretical Ecology, 2013)

Neophobia and social tolerance are related to breeding group size in a semi-colonial bird - Sophie Dardenne; Simon Ducatez; Julien Cote; Pascal Poncin; Virginie M. Stevens (Behavioral Ecology and Sociobiology, 2013)

Recent advances in 2D and 3D in vitro systems using primary hepatocytes, alternative hepatocyte sources and non-parenchymal liver cells and their use in investigating mechanisms of hepatotoxicity, cell signaling and ADME - Patricio Godoy; Nicola J. Hewitt; Ute Albrecht; Melvin E. Andersen; Nariman Ansari; Sudin Bhattacharya; Johannes Georg Bode; Jennifer Bolleyn; Christoph Borner; Jan Böttger; Albert Braeuning; Robert A. Budinsky; et al. (Archives of Toxicology, 2013)

A global quantitative synthesis of local and landscape effects on wild bee pollinators in agroecosystems - Christina M. Kennedy; Eric Lonsdorf; Maile C. Neel; Neal M. Williams; Taylor H. Ricketts; Rachael Winfree; Riccardo Bommarco; Claire Brittain; Alana L. Burley; Daniel Cariveau; Luísa G. Carvalheiro; Natacha P. Chacoff; et al. (Ecology Letters, 2013)
Bees provide essential pollination services that are potentially affected both by local farm management and the surrounding landscape. To better understand these different factors, we modelled the relative effects of landscape composition (nesting and floral resources within foraging distances), landscape configuration (patch shape, interpatch connectivity and habitat aggregation) and farm management (organic vs. conventional and local‐scale field diversity), and their interactions, on wild bee abundance and richness for 39 crop systems globally. Bee abundance and richness were higher in diversified and organic fields and in landscapes comprising more high‐quality habitats; bee richness on conventional fields with low diversity benefited most from high‐quality surrounding land cover. Landscape configuration effects were weak. Bee responses varied slightly by biome. Our synthesis reveals that pollinator persistence will depend on both the maintenance of high‐quality habitats around farms and on local management practices that may offset impacts of intensive monoculture agriculture.

Erratum to: Magnetic Nanoparticle Targeted Hyperthermia of Cutaneous Staphylococcus aureus Infection - Min-Ho Kim; Itsukyo Yamayoshi; Steven Mathew; Hubert Lin; Joseph Nayfach; Scott I. Simon (Annals of Biomedical Engineering, 2013)

Magnetic Nanoparticle Targeted Hyperthermia of Cutaneous Staphylococcus aureus Infection - Min-Ho Kim; Itsukyo Yamayoshi; Steven Mathew; Hubert Lin; Joseph Nayfach; Scott I. Simon (Annals of Biomedical Engineering, 2013)

Biological functions of ecto-enzymes in regulating extracellular adenosine levels in neoplastic and inflammatory disease states - Maria Serena Longhi; Simon C. Robson; Steven H. Bernstein; Sara Serra; Silvia Deaglio (Journal of Molecular Medicine, 2013)

Genome-wide association study of glioma and meta-analysis - Preetha Rajaraman; Beatrice S. Melin; Zhaoming Wang; Roberta McKean-Cowdin; Dominique S. Michaud; Sophia S. Wang; Melissa Bondy; Richard Houlston; Robert B. Jenkins; Margaret Wrensch; Meredith Yeager; Anders Ahlbom; et al. (Human Genetics, 2012)

Connecting dynamic vegetation models to data – an inverse perspective - Florian Hartig; James Dyke; Thomas Hickler; Steven I. Higgins; Robert B. O’Hara; Simon Scheiter; Andreas Huth (Journal of Biogeography, 2012)
Dynamic vegetation models provide process‐based explanations of the dynamics and the distribution of plant ecosystems. They offer significant advantages over static, correlative modelling approaches, particularly for ecosystems that are outside their equilibrium due to global change or climate change. A persistent problem, however, is their parameterization. Parameters and processes of dynamic vegetation models (DVMs) are traditionally determined independently of the model, while model outputs are compared to empirical data for validation and informal model comparison only. But field data for such independent estimates of parameters and processes are often difficult to obtain, and the desire to include better descriptions of processes such as biotic interactions, dispersal, phenotypic plasticity and evolution in future vegetation models aggravates limitations related to the current parameterization paradigm. In this paper, we discuss the use of Bayesian methods to bridge this gap. We explain how Bayesian methods allow direct estimates of parameters and processes, encoded in prior distributions, to be combined with inverse estimates, encoded in likelihood functions. The combination of direct and inverse estimation of parameters and processes allows a much wider range of vegetation data to be used simultaneously, including vegetation inventories, species traits, species distributions, remote sensing, eddy flux measurements and palaeorecords. The possible reduction of uncertainty regarding structure, parameters and predictions of DVMs may not only foster scientific progress, but will also increase the relevance of these models for policy advice.

A physiological analogy of the niche for projecting the potential distribution of plants - Steven I. Higgins; Robert B. O’Hara; Olga Bykova; Michael D. Cramer; Isabelle Chuine; Eva‐Maria Gerstner; Thomas Hickler; Xavier Morin; Michael R. Kearney; Guy F. Midgley; Simon Scheiter (Journal of Biogeography, 2012)
Aim To develop a physiologically based model of the plant niche for use in species distribution modelling. Location Europe. Methods We link the Thornley transport resistance (TTR) model with functions which describe how the TTR’s model parameters are influenced by abiotic environmental factors. The TTR model considers how carbon and nutrient uptake, and the allocation of these assimilates, influence growth. We use indirect statistical methods to estimate the model parameters from a high resolution data set on tree distribution for 22 European tree species. Results We infer, from distribution data and abiotic forcing data, the physiological niche dimensions of 22 European tree species. We found that the model fits were reasonable (AUC: 0.79–0.964). The projected distributions were characterized by a false positive rate of 0.19 and a false negative rate 0.12. The fitted models are used to generate projections of the environmental factors that limit the range boundaries of the study species. Main conclusions We show that physiological models can be used to derive physiological niche dimensions from species distribution data. Future work should focus on including prior information on physiological rates into the parameter estimation process. Application of the TTR model to species distribution modelling suggests new avenues for establishing explicit links between distribution and physiology, and for generating hypotheses about how ecophysiological processes influence the distribution of plants.

Preclinical assessment of an adjunctive treatment approach for cognitive impairment associated with schizophrenia using the alpha7 nicotinic acetylcholine receptor agonist WYE-103914/SEN34625 - Karen L. Marquis; Thomas A. Comery; Flora Jow; Rachel L. Navarra; Steven M. Grauer; Claudine Pulicicchio; Cody Kelley; Julie A. Brennan; Renza Roncarati; Carla Scali; Simon Haydar; Chiara Ghiron; et al. (Psychopharmacology, 2011)

Tracking and mapping sun-synchronous migrations and diel space use patterns of Haemulon sciurus and Lutjanus apodus in the U.S. Virgin Islands - Steven Hitt; Simon J. Pittman; Kerry A. Brown (Environmental Biology of Fishes, 2011)

Development of S/MAR minicircles for enhanced and persistent transgene expression in the mouse liver - Orestis Argyros; Suet Ping Wong; Constantinos Fedonidis; Oleg Tolmachov; Simon N. Waddington; Steven J. Howe; Marcello Niceta; Charles Coutelle; Richard P. Harbottle (Journal of Molecular Medicine, 2011)

How does the genetic assassin select its neuronal target? - James C. Stevens; Elizabeth M. C. Fisher; Simon Mead (Mammalian Genome, 2011)

Polymorphisms in oxidative stress and inflammation pathway genes, low-dose ionizing radiation, and the risk of breast cancer among US radiologic technologists - Sara J. Schonfeld; Parveen Bhatti; Elizabeth E. Brown; Martha S. Linet; Steven L. Simon; Robert M. Weinstock; Amy A. Hutchinson; Marilyn Stovall; Dale L. Preston; Bruce H. Alexander; Michele M. Doody; Alice J. Sigurdson (Cancer Causes & Control, 2010)

The roles of surface heat flux and ocean heat transport convergence in determining Atlantic Ocean temperature variability - Jeremy P. Grist; Simon A. Josey; Robert Marsh; Simon A. Good; Andrew. C. Coward; Beverly A. de Cuevas; Steven G. Alderson; Adrian L. New; Gurvan Madec (Ocean Dynamics, 2010)

The stability of African savannas: insights from the indirect estimation of the parameters of a dynamic model - Steven I. Higgins; Simon Scheiter; Mahesh Sankaran (Ecology, 2010)
Savannas are characterized by a competitive tension between grasses and trees, and theoretical models illustrate how this competitive tension is influenced by resource availability, competition for these resources, and disturbances. How this universe of theoretical possibilities translates into the real world is, however, poorly understood. In this paper we indirectly parameterize a theoretical model of savanna dynamics with the aim of gaining insights as to how the grass–tree balance changes across a broad biogeographical gradient. We use data on the abundance of trees in African savannas and Markov chain Monte Carlo methods to estimate the model parameters. The analysis shows that grasses and trees can coexist over a broad range of rainfall regimes. Further, our results indicate that savannas may be regulated by either asymptotically stable dynamics (in the absence of fire) or by stable limit cycles (in the presence of fire). Rainfall does not influence which of these two classes of dynamics occurs. We conclude that, even though fire might not be necessary for grass–tree coexistence, it nonetheless is an important modifier of grass : tree ratios.

A genetic basis for the phenotypic differentiation between siscowet and lean lake trout ( Salvelinus namaycush ) - FREDERICK GOETZ; DANIEL ROSAUER; SHAWN SITAR; GILES GOETZ; CRYSTAL SIMCHICK; STEVEN ROBERTS; RONALD JOHNSON; CHERYL MURPHY; CHARLES R. BRONTE; SIMON MACKENZIE (Molecular Ecology, 2010)
In Lake Superior there are three principal forms of lake trout ( Salvelinus namaycush ): lean, siscowet and humper. Wild lean and siscowet differ in the shape and relative size of the head, size of the fins, location and size of the eyes, caudal peduncle shape and lipid content of the musculature. To investigate the basis for these phenotypic differences, lean and siscowet lake trout, derived from gametes of wild populations in Lake Superior, were reared communally under identical environmental conditions for 2.5 years. Fish were analysed for growth, morphometry and lipid content, and differences in liver transcriptomics were investigated using Roche 454 GS‐FLX pyrosequencing. The results demonstrate that key phenotypic differences between wild lean and siscowet lake trout such as condition factor, morphometry and lipid levels, persist in these two forms when reared in the laboratory under identical environmental conditions. This strongly suggests that these differences are genetic and not a result of environmental plasticity. Transcriptomic analysis involving the comparison of hepatic gene frequencies (RNA‐seq) and expression (quantitative reverse transcription–polymerase chain reaction (qPCR)) between the two lake trout forms, indicated two primary gene groups that were differentially expressed; those involving lipid synthesis, metabolism and transport (acyl‐CoA desaturase, acyl‐CoA binding protein, peroxisome proliferator‐activated receptor gamma, and apolipoproteins), and those involved with immunity (complement component C3, proteasome, FK506 binding protein 5 and C1q proteins). The results demonstrate that RNA‐seq can be used to identify differentially expressed genes; however, some discrepancies between RNA‐seq analysis and qPCR indicate that methods for deep sequencing may need to be refined and/or different RNA‐seq platforms utilized.

Breeding systems and phylogenetic diversity of seed plants along a large‐scale elevational gradient - Steven M. Vamosi; Simon A. Queenborough (Journal of Biogeography, 2010)
Aim The factors affecting the distribution of dioecious species have received surprisingly little attention and, as a consequence, are poorly understood. For example, there is a well‐documented negative association between dioecy and latitude, for which we have no candidate mechanisms. Conversely, it has been suggested that the relative proportion of dioecious species should be positively correlated with changes in elevation. Location Costa Rica, Central America. Methods We made use of data on the distribution of 175 seed plant species from a series of plots along a transect in Costa Rica that ranged from 30 to 2600 m a.s.l. to test the prediction that dioecy is correlated with elevation. Specifically, we examined relationships between the proportion of dioecy, at the species and individual levels, and the elevation, species richness, number of individuals, and phylogenetic diversity (PD) of plots. For comparison, we repeated all analyses with monoecious species, which also have unisexual flowers but do not suffer from reduced mate assurance and the seed shadow effect that may be the outcomes of having spatially separated sexes. Results The relative proportions of dioecious species and individuals displayed a unimodal relationship with elevation, both peaking at 750 m a.s.l. In contrast, the relative proportions of monoecious species and individuals displayed negative associations with elevation. In addition, the proportion of dioecious species was significantly positively associated with species richness and with the PD of plots. The proportion of monoecious species was not associated with species richness and was weakly positively associated with the PD of plots. Main conclusions Our results suggest that the selection pressure of elevation on the pollinators and life‐history strategy of dioecious species is much less than expected, and is overshadowed by the as‐yet unexplained correlation of dioecy with species richness. Additional studies of the ecology of cosexual and unisexual (i.e. dioecious and monoecious) species along large environmental gradients are needed.

Nitrogen deposition causes widespread loss of species richness in British habitats - LINDSAY C. MASKELL; SIMON M. SMART; JAMES M. BULLOCK; KEN THOMPSON; CARLY J. STEVENS (Global Change Biology, 2010)
We use national scale data to test the hypothesis that nitrogen (N) deposition is strongly negatively correlated with plant species richness in a wide range of ecosystem types. Vegetation plots from a national ecological surveillance programme were drawn from heathland, acid, calcareous and mesotrophic grassland habitats. Mean species number and mean plant traits were calculated for each plot and related to atmospheric N deposition. There was a significant reduction in species richness with N deposition in acid grassland and heathland even after fitting covarying factors. In acid grassland and heathland, evidence from trait changes suggested that acidification rather than increased fertility was responsible for species loss. In contrast, calcareous grassland showed evidence of eutrophication in response to increasing N deposition. Loss of species richness from chronic N deposition is apparent in infertile grasslands and heathland. Mechanisms associated with loss of species richness differ between habitats so mitigation of N deposition should be targeted to habitat type.

Impacts of climate change on the vegetation of Africa: an adaptive dynamic vegetation modelling approach - SIMON SCHEITER; STEVEN I. HIGGINS (Global Change Biology, 2009)
Recent IPCC projections suggest that Africa will be subject to particularly severe changes in atmospheric conditions. How the vegetation of Africa and particularly the grassland–savanna–forest complex will respond to these changes has rarely been investigated. Most studies on global carbon cycles use vegetation models that do not adequately account for the complexity of the interactions that shape the distribution of tropical grasslands, savannas and forests. This casts doubt on their ability to reliably simulate the future vegetation of Africa. We present a new vegetation model, the adaptive dynamic global vegetation model (aDGVM) that was specifically developed for tropical vegetation. The aDGVM combines established components from existing DGVMs with novel process‐based and adaptive modules for phenology, carbon allocation and fire within an individual‐based framework. Thus, the model allows vegetation to adapt phenology, allocation and physiology to changing environmental conditions and disturbances in a way not possible in models based on fixed functional types. We used the model to simulate the current vegetation patterns of Africa and found good agreement between model projections and vegetation maps. We simulated vegetation in absence of fire and found that fire suppression strongly influences tree dominance at the regional scale while at a continental scale fire suppression increases biomass in vegetation by a more modest 13%. Simulations under elevated temperature and atmospheric CO 2 concentrations predicted longer growing periods, higher allocation to roots, higher fecundity, more biomass and a dramatic shift toward tree dominated biomes. Our analyses suggest that the CO 2 fertilization effect is not saturated at ambient CO 2 levels and will strongly increase in response to further increases in CO 2 levels. The model provides a general and flexible framework for describing vegetation response to the interactive effects of climate and disturbances.

Cultivable bacteria from bulk water, aggregates, and surface sediments of a tidal flat ecosystem - Heike Stevens; Meinhard Simon; Thorsten Brinkhoff (Ocean Dynamics, 2009)

Towards a worldwide wood economics spectrum - Jerome Chave; David Coomes; Steven Jansen; Simon L. Lewis; Nathan G. Swenson; Amy E. Zanne (Ecology Letters, 2009)
Wood performs several essential functions in plants, including mechanically supporting aboveground tissue, storing water and other resources, and transporting sap. Woody tissues are likely to face physiological, structural and defensive trade‐offs. How a plant optimizes among these competing functions can have major ecological implications, which have been under‐appreciated by ecologists compared to the focus they have given to leaf function. To draw together our current understanding of wood function, we identify and collate data on the major wood functional traits, including the largest wood density database to date (8412 taxa), mechanical strength measures and anatomical features, as well as clade‐specific features such as secondary chemistry. We then show how wood traits are related to one another, highlighting functional trade‐offs, and to ecological and demographic plant features (growth form, growth rate, latitude, ecological setting). We suggest that, similar to the manifold that tree species leaf traits cluster around the ‘leaf economics spectrum’, a similar ‘wood economics spectrum’ may be defined. We then discuss the biogeography, evolution and biogeochemistry of the spectrum, and conclude by pointing out the major gaps in our current knowledge of wood functional traits.

A Neisseria meningitidis NMB1966 mutant is impaired for invasion of respiratory epithelial cells, survival in human blood and for virulence in vivo - Ming-Shi Li; Noel Y. S. Chow; Sunita Sinha; Denise Halliwell; Michelle Finney; Andrew R. Gorringe; Mark W. Watson; J. Simon Kroll; Paul R. Langford; Steven A. R. Webb (Medical Microbiology and Immunology, 2009)

Diversity and abundance of Gram positive bacteria in a tidal flat ecosystem - Heike Stevens; Thorsten Brinkhoff; Beate Rink; John Vollmers; Meinhard Simon (Environmental Microbiology, 2007)
Summary Gram positive bacteria recently have been identified as important components of freshwater ecosystems and are also present in marine environments. However, their quantitative significance and possible role in the latter systems is still little studied, in particular in coastal regions. Therefore, we investigated the abundance and composition of Gram positive bacteria in the Wadden Sea, a tidal flat ecosystem in the German Bight of the North Sea. Applying fluorescence in situ hybridization we found that Actinobacteria constitute 4–7% of total bacteria in the Wadden Sea and slightly higher proportions in a freshwater drainage channel connected to the sea by a sluice. The application of denaturing gradient gel electrophoresis of 16S rRNA gene fragments after amplification by an Actinobacteria ‐specific primer set and subsequent sequencing showed that the composition of the actinobacterial community in the Wadden Sea was distinctly different from that in the freshwater system. A bacterial clone library of 111 clones yielded eight Gram positive phylotypes which are related closely to other marine phylotypes including the Marine Actinobacteria Clade but also to freshwater phylotypes. We applied dilution cultures, enriched with various biopolymers, Marine Broth and Fucus vesiculosus extracts, for isolating bacteria from the bulk water, suspended aggregates, the oxic surface and oxic/anoxic transition zone of the sediment. Fifty‐three isolates affiliated to seven families of the order Actinomycetales and nine isolates to the family Bacillaceae . The salinity range (1–45‰ NaCl) and growth optimum of 14 strains from various families showed that all except one strain exhibited a rather broad range of sustained growth from 1‰ to ≥ 20‰ NaCl and several strains exhibited an optimum of > 10‰ NaCl. The results indicate that the Gram positive bacterial community in the Wadden Sea is surprisingly diverse and consists mainly of indigenous species which appear to be well adapted to the environmental conditions of this coastal ecosystem.

Oculopharyngeal muscular dystrophy (OPMD): analysis of the PABPN1 gene expansion sequence in 86 patients reveals 13 different expansion types and further evidence for unequal recombination as the mutational mechanism - David O. Robinson; Simon R. Hammans; Steven P. Read; Julie Sillibourne (Human Genetics, 2005)

Organization of the MASP2 locus and its expression profile in mouse and rat - Cordula M. Stover; Nicholas J. Lynch; Steven J. Hanson; Michaela Windbichler; Simon G. Gregory; Wilhelm J. Schwaeble (Mammalian Genome, 2004)

Acetohydroxyacid synthase mutations conferring resistance to imidazolinone or sulfonylurea herbicides in sunflower - Judith M. Kolkman; Mary B. Slabaugh; Jose M. Bruniard; Simon Berry; B. Shaun Bushman; Christine Olungu; Nele Maes; Gustavo Abratti; Andres Zambelli; Jerry F. Miller; Alberto Leon; Steven J. Knapp (Theoretical and Applied Genetics, 2004)

c-fos induction in rat superficial dorsal horn following cutaneous application of noxious chemical or mechanical stimuli - Steven L. Jinks; Christopher T. Simons; Jean-Marc Dessirier; Mirela Iodi Carstens; Joseph F. Antognini; E. Carstens (Experimental Brain Research, 2002)

Analgesia induced by chronic nicotine infusion in rats - Carstens E.; Kenton Anderson; Christopher Simons; Mirela Carstens; Steven Jinks (Psychopharmacology, 2001)

40Ar/39Ar ages in deformed potassium feldspar: evidence of microstructural control on Ar isotope systematics - Steven M. Reddy; Graham J. Potts; Simon P. Kelley (Contributions to Mineralogy and Petrology, 2001)

Role of neuronal nicotinic-acetylcholine receptors in the activation of neurons in trigeminal subnucleus caudalis by nicotine delivered to the oral mucosa - E. Carstens; Christopher T. Simons; Jean-Marc Dessirier; M. Iodi Carstens; Steven L. Jinks (Experimental Brain Research, 2000)

Tree-Growth and Understory Responses to Low-Severity Prescribed Burning in Thinned Pinus ponderosa Forests of Central Oregon - Matt D. Busse; Steven A. Simon; Gregg M. Riegel (Forest Science, 2000)
The growth of ponderosa pine and associated understory vegetation was evaluated for a 6 yr period following spring underburning of surface fuels. Underburn and control (unburned) plots were paired at 15 replicate sites in pole-sized ponderosa pine forests of central Oregon. The burns were generally low in severity, as noted by low 0 horizon mass reduction (24%) and tree mortality (6%). A small but significant decline in basal area and volume growth rates of surviving trees was found in the 6 yr following underburning. The reduction in tree growth was related to a combination of crown length reduction, 0 horizon reduction, and site productivity. More productive stands had the highest proportional reduction in growth due to burning. By comparison, site conditions including stand density, initial basal area, elevation, parent material, and soil fertility were not related to the observed growth reduction. Understory vegetation showed a mixed response to burning. Shrub cover, dominated by Purshia tridentata, declined significantly following burning and remained well below preburn levels for the length of the study, even though one-fourth of all burned Purshia plants successfully resprouted. Total herbaceous vegetation cover and production were unaffected by burning, while species diversity increased slightly. With the exception of the decline in Purshia cover, the results indicate that low-severity prescribed burning has a relatively minor impact on tree-growth and understory response in thinned ponderosa pine stands. For. Sci. 46(2):258-268.

Diversity and habitat relationships of hypogeous fungi. II. Factors influencing the occurrence and number of taxa - Andrew W. Claridge; Simon C. Barry; Steven J. Cork; James M. Trappe (Biodiversity and Conservation, 2000)

Trace element signatures in otoliths record natal river of juvenile American shad ( Alosa sapidissima ) - Simon R. Thorrold; Cynthia M. Jones; Steven E. Campana; James W. McLaren; Joseph W. H. Lam (Limnology and Oceanography, 1998)
The elemental composition of fish otoliths may represent a permanent record of the environmental conditions an individual has experienced as trace elements, incorporated into the growing surface of the otolith, reflect the physical and chemical characteristics of the ambient water. We tested the utility of trace element signatures in otoliths as natural tags of the river of origin of juvenile American shad ( Alosa sapidissima ) collected from the Connecticut, Hudson and Delaware Rivers in August and October 1994. Four elements (K, Mn, Sr, and Ba) showed significant variability among sites within rivers in August, although only Mg showed a significant site effect by October. Four elements (Mg, Mn, Sr, and Ba) differed significantly among rivers in both months. Linear discriminant functions based on the trace element signatures classified fish to their natal river with ~90% accuracy in both August and October collections. The discriminant function generated from the August data was able to classify fish collected in October successfully with better than 80% accuracy. On the basis of our findings, the river of origin of adult fish could be accurately determined by quantifying the trace element composition of the juvenile portion of their otoliths.

Eucalyptus has a functional equivalent of the Arabidopsis floral meristem identity gene LEAFY - Simon G. Southerton; Steven H. Strauss; Mark R. Olive; Rebecca L. Harcourt; Veronique Decroocq; Xiaomei Zhu; Danny J. Llewellyn; W. James Peacock; Elizabeth S. Dennis (Plant Molecular Biology, 1998)

Identifying novel regulators of shoot meristem development - Jeffrey A. Pogany; Ephraim J. Simon; Rebecca B. Katzman; Bernadette M. De Guzman; Lita Po Yu; Amy E. Trotochaud; Steven E. Clark (Journal of Plant Research, 1998)

A microstructural and argon laserprobe study of shear zone development at the western margin of the Nanga Parbat-Haramosh Massif, western Himalaya - Steven M. Reddy; Simon P. Kelley; Lochlann Magennis (Contributions to Mineralogy and Petrology, 1997)

Structure and mechanism of galactose oxidase: catalytic role of tyrosine 495 - Mark P. Reynolds; Andrew J. Baron; Carrie M. Wilmot; Elinor Vinecombe; Conrad Stevens; Simon E. V. Phillips; Peter F. Knowles; M. J. McPherson (JBIC Journal of Biological Inorganic Chemistry, 1997)

Response of otolith microchemistry to environmental variations experienced by larval and juvenile Atlantic croaker (Micropogonias undulatus) - Simon R. Thorrold; Cynthia M. Jones; Steven E. Campana (Limnology and Oceanography, 1997)
Minor and trace elements incorporated into otoliths during growth may permanently record environmental conditions experienced by fishes. To determine the validity of this approach, we used laser ablation inductively coupled plasma mass spectrometry (LA‐ICPMS) to assay sectioned otoliths from juvenile Atlantic croaker ( Micropogonias undulatus ) collected from each of three sites in the Neuse River, North Carolina, and the Elizabeth River, Virginia. Elemental concentrations at the center of the otoliths did not differ between locations, although both Mg:Ca and Ba:Ca were significantly higher at the edge of otoliths from the Neuse River than from the Elizabeth River. Three of the elements (Mg:Ca, Sr:Ca, and Ba:Ca) showed significant variation across otoliths. Sr:Ca, and to a lesser extent Mg:Ca, showed progressive decreases as the fish moved from offshore spawning sites to estuarine nursery areas. The opposite pattern was shown by Ba: Ca. We hypothesize that: these patterns were related to the elemental concentrations within oceanic and estuarine water masses. Although both Sr: Ca and Ba: Ca seem to be useful tracers of offshore‐inshore migration of estuarine‐dependent species, the sensitivity of the technique to more subtle changes in water chemistry remains to be determined.